Assessing smallholder sustainable intensification in the Ethiopian highlands - Hammond, James; Wijk, Mark T. van; Teufel, Nils; Mekonnen, Kindu; Thorne, Peter J. (Elsevier, 2021)
Sustainable intensification is one approach to increasing food production without undermining sustainability goals. In recent years new tools and indicators have been developed for broad-based assessment of sustainable intensification. However, most of these tools have been applied at field level and assessing individual technologies, while integrated assessments of multiple novel practices at farm-to-village level are lacking. In this study we develop and apply a data collection, analysis, and interpretation approach that results in a replicable and rapid method for a multi-variate assessment of sustainable intensification. Drawing on a survey of 779 participant farmers, and using the Sustainable Intensification Assessment Framework, we quantified 27 indicators grouped into five domains: agricultural production, economics, environment, human welfare, and social. We applied an expert-led threshold setting exercise to re-scale indicators, permitting aggregated and dis-aggregated visualisation onto a common axis. We developed a graphic evaluation approach to communicate the multiple domain and indicator scores and applied this approach to quantify trade-offs and synergies related to agricultural productivity in four contrasting sites in Ethiopia. In each site there was a notable and significant gradient of production intensity, although average crop and livestock productivity remained well below attainable levels. Higher levels of productivity were correlated with higher scores in the economic, social and agricultural domains, and in some sites they were also positively correlated with the human welfare and environmental domains. In no case was increased production intensity correlated with lower scores in any of the sustainability domains, indicating that in these relatively low-intensity systems increases in productivity will go hand-in-hand with improvements in most other sustainability domains. Synergies can overrule trade-offs in these smallholder systems in Ethiopia, if managed well. This is one of very few studies of multiple sustainable intensification technologies implemented concurrently at the household to community level. Most studies focus on individual technologies or practices within specific niches of the farming system. The method could be developed further for efficient application to various large-scale development or intensification projects, and could potentially make use of existing smallholder information databases. An assessment of sustainable intensification in one district (woreda) of central Ethiopia. The boxplot in the upper left of the figure shows the condition of five “sustainability domains”, which are: agricultural production, economic, environment, human welfare, and social. The point plot in the upper right of the figure shows the median and inter-quartile range of each of the indicators monitored. The indicators used are listed on the right hand side of the figure. The table in the lower part of the figure provides framework for prioritisation of issues, whereby indicators with worse overall status may be considered more urgent, and indicators with low variation within the site may be considered more challenging to influence. • A five-year program promoting multiple concurrent sustainable intensification technologies was assessed. • Farm productivity was correlated to improvements in the other sustainability domains, indicating a lack of trade-offs. • Synergies due to the initially low productivity, the wide range of technologies, and the meaningful farmer participation. • Crop and livestock productivity was still below attainable levels, and progress was not uniform amongst participants. • The method presented here is suitable to monitor the transition towards sustainable intensification in portfolio programs.